INVESTIGASI EKSPERIMENTAL PERFORMA SISTEM PENDINGIN MULTI-TERMOELEKTRIK DENGAN KONFIGURASI TERMAL SERI DAN PARALEL - Bowo Yuli Prasetyo; Apip Badarudin; A.P. Edi Sukamto; Rizki Muliawan (Jurnal Teknologi Terapan, 2022)
Thermoelectrics can convert electrical energy to thermal energy. The generated thermal energy can be used in various cooling systems (TEC) applications. Improvement of TEC performance influenced by hot-side heat dissipation method, working fluid, and multi-thermoelectric. This study aims to investigate the relation between multi-thermoelectric configuration and the cooling behaviors. The experiment was conducted on the devices equipped with two modules of TEC arranged in series and parallel with variations of input voltage, working fluid mass flow, and temperature. The result reveals variations in cooling behaviors between the two configurations. Parallel configuration TEC gives the highest cooling capacity with a value of 66.62 W, 100% bigger than the series configuration. Meanwhile, the series configuration provides a delta temperature of 11.03 K, 2% higher than the parallel one. The parallel modules cooling performance is the biggest among the two arrangement, with a value of 2.57, which is 147% higher than series one.